2007
DOI: 10.1161/01.hyp.0000259666.99449.74
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic Inputs in the Hypothalamic Paraventricular Nucleus Maintain Sympathetic Vasomotor Tone in Hypertension

Abstract: Abstract-The paraventricular nucleus (PVN) of the hypothalamus is critical to the regulation of sympathetic output. The PVN hyperactivity is known to cause increased sympathetic nerve activity in spontaneously hypertensive rats (SHRs). The purpose of this study was to determine whether glutamatergic input to the PVN contributes to heightened sympathetic outflow in hypertension. Lumbar sympathetic nerve activity, mean arterial blood pressure, and heart rate were recorded from anesthetized SHRs and Wistar-Kyoto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
175
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(183 citation statements)
references
References 52 publications
8
175
0
Order By: Relevance
“…It is possible that the alteration in NMDA mRNA expression in the hypothalamus might be related to the reduced sympathetic activity in FF+A7, and as a consequence, the reduced cardiac sympathetic tone, the improvement on baroreflex control of HR, and the improvement on glucose metabolism observed in these rats. Increased NMDA activity has been related to the higher sympathoexcitation during hypertension 47 or heart failure. 48 Another possibility would be the reduction of the activity of hypothalamic neurons directly related to the energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the alteration in NMDA mRNA expression in the hypothalamus might be related to the reduced sympathetic activity in FF+A7, and as a consequence, the reduced cardiac sympathetic tone, the improvement on baroreflex control of HR, and the improvement on glucose metabolism observed in these rats. Increased NMDA activity has been related to the higher sympathoexcitation during hypertension 47 or heart failure. 48 Another possibility would be the reduction of the activity of hypothalamic neurons directly related to the energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reductions of SNA in response to PVN inhibition or blockade of excitatory inputs are more pronounced in water deprived (Freeman and Brooks 2007;Stocker et al 2004b and hypertensive (Allen 2002;Li and Pan 2007) rats. These findings indicate that PVN neuronal activity contributes to both the maintenance of resting SNA and to the elevation of SNA under physiologic and disease conditions.…”
Section: Pvn-rvlm and Pvn-rvlm/iml Neurons And Support Of Sympatheticmentioning
confidence: 98%
“…Over the past several years, studies have increasingly focused on the role of PVN neurons in regulating sympathetic nerve activity (SNA) (Akine et al 2003;Allen 2002;Li and Pan 2007;Li et al 2006;Lovick and Coote 1988b;Porter and Brody 1985;Stern 2004;Toney et al 2003). Early studies showed that stimulation of the PVN reduces visceral organ blood flow and increases arterial blood pressure (ABP) (Martin and Haywood 1992;Porter andBrody 1985, 1986), whereas disinhibition of the PVN by GABA A receptor blockade increases ABP, heart rate, and plasma norepinephrine concentration (Martin and Haywood 1993;Martin et al 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Inhibiting the PVN dramatically reduces sympathetic vasomotor tone, 7 whereas activating the PVN increases sympathetic outflow in SHR. 8 Bilateral electrolytic lesions of the PVN attenuate the sympathetic activity and the development of hypertension in SHR. 9,10 These results indicate the importance of the PVN in the development and progression of hypertension in SHR.…”
Section: Introductionmentioning
confidence: 99%